Association Between Protein Intake and Stunting Among Children Aged 6–24 Months in the Bagi Community Health Center Catchment Area, Central Lombok Regency - Rafly, Muhammad; Nurbaiti, Lina; Lastyaana, Wiwin (Jurnal Biologi Tropis, 2026)
Stunting is still a long-term nutritional issue and a significant concern for public health, especially in children younger than two years. Protein is a vital nutrient that is important for growth in height; however, the information about its relationship with stunting is not consistent. Understanding this relationship is crucial for designing effective nutritional interventions. A cross-sectional study was conducted involving 43 children who met the inclusion and exclusion criteria. Protein intake was assessed using a 1×24-hour food recall and analyzed with NutriSurvey software. Stunting status was determined based on height/length-for-age (HAZ) according to WHO standards. The association between protein intake and stunting was analyzed using the Chi-Square test with the Monte Carlo Exact method. The results of the study showed that of all toddlers studied, 62.8% experienced stunting and 37.2% experienced severe stunting. The majority of toddlers had good protein intake (55.8%). Statistical evaluation through the Chi-Square test with the Exact (Monte Carlo) method indicated that there was no meaningful connection between protein consumption and the occurrence of stunting (p = 0.584). In the region served by Bagu Community Health Center, Central Lombok Regency, there was no significant association between protein intake and the prevalence of stunting in children aged 6–24 months.